Introduction to topology and geometry - Stahl, Saul.; Stenson, Catherine, 1972- (Hoboken, New Jersey : Wiley, 2013)
"Presenting upper graduate level material in an accessible way for undergraduates, this Second Edition strikes a welcome balance between academic rigor and accessibility while covering an unparalleled range of topics, including the elements of projective geometry, conics and the applications and properties of conic selections, cross ratio points of infinity and fundamental transformations of projective geometry, the points of a homography/involution, and more. In addition, this comprehensive book includes numerous exercises and historical notes"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Topology; Geometry; MATHEMATICS -- Topology; Geometry; Topology; Topologie; Online-Publikation; Geometrie; Electronic books; Electronic books